Review: Beyond Nancy Drew: U.S. Girls’ Series Fiction in the Twentieth Century - Rebekah Fitzsimmons (International Journal of Young Adult Literature)
In lieu of an abstract: When I was asked to review Beyond Nancy Drew: U.S. Girls’ Series Fiction in the Twentieth Century, I had to pause and really consider whether I could be objective or whether my nostalgic love for the Nancy Drew series might cloud my judgement. Growing up, my grandparents’ home featured shelves and shelves of books, including a full shelf of Nancy Drew and Bobbsey Twins books. The books were bound in matching blue tweed covers with decorative details on the spine, in what my scholarly-trained mind’s eye now recognizes as a publisher’s play for middlebrow respectability. The uniform size, binding, and height of both book series offered a decorative element and fit in well with the shelves of encyclopedias, back issues of National Geographic (arranged in date order), and mass-produced copies of Western classics with faux leather bindings. When I was old enough, I devoured every copy of Nancy Drew on that shelf; The Mystery at Lilac Inn was and remains my favorite. As I got older, I read further in the series and moved into the slightly older and more contemporary (i.e. sexy and soap-opera-esque) Nancy Drew Files. I read other series fiction, namely The Baby-Sitters Club, and then eventually found YA dystopian trilogies. I certainly feel comfortable ascribing much of my professional interest in children’s and young adult literature to those copies of Nancy Drew. (I also harbor a deeply hidden desire to one day be described as ‘plucky’, but that is, perhaps, a different essay.)